Clinical characteristics and the risk factors for the exacerbation of symptoms in patients with inflammatory bowel disease during the COVID-19 pandemic - Wu, Juan; Fang, Yuanyuan; Bai, Bingqing; Wu, Yumei; Liu, Qiuyuan; Hu, Jing; Hu, Naizhong; Mei, Qiao; Han, Wei (Frontiers in Medicine, 2024)
Background: In 2023, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant caused a large-scale outbreak of coronavirus disease 2019 in China. It is not clear the risk factors that lead to the exacerbation of symptoms in patients with inflammatory bowel disease (IBD) after COVID-19 infection. Our study aims to find out the risk factors for the exacerbation of IBD-related symptoms in IBD patients with COVID-19 infection and to provide guidance for the clinical management of IBD. Methods: This is a retrospective, observational study. The online questionnaire was distributed to conduct a survey to collect demographic, clinical, and IBD related characteristics in IBD patients. Univariate and multivariate regression analyses was conducted to assess the independent effects. Results: In total, 534 cases of IBD patients were analyzed in our study. Among them, 466 (87.3%) cases diagnosed with COVID-19, 160 (34.3%) cases experienced exacerbation of IBD symptoms, and 84 (18.0%) patients opted for medication discontinuation. Male sex (OR 2.04, 95% CI 1.34-3.49, p=0.001) and the decrease in body mass index (BMI) (OR 0.93, 95% CI 0.87-1.00, p=0.035) were positively correlated with the exacerbation of IBD symptoms. Furthermore, the medication discontinuation (OR 2.60, 95% CI 1.58-4.30, p<0.001) was strongly positively correlated with the exacerbation of IBD symptoms. No significant association was seen between age, comorbidities, smoking, disease activity, vaccination, therapy for COVID-19 and the worsening of IBD symptoms.This study confirms that the infection rate of COVID-19 in China IBD patients was comparable to the general population. Male sex, the decrease in BMI and medication discontinuation are significant risk factors for the exacerbation of IBD-related symptoms in IBD patients with COVID-19 infection.